1998
DOI: 10.1590/s0100-879x1998000500016
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory adaptations induced by aerobic training in middle-aged men: the importance of a decrease in sympathetic stimulation for the contribution of dynamic exercise tachycardia

Abstract: We investigated the effects of aerobic training on the efferent autonomic control of heart rate (HR) during dynamic exercise in middleaged men, eight of whom underwent exercise training (T) while the other seven continued their sedentary (S) life style. The training was conducted over 10 months (three 1-h/sessions/week on a field track at 70-85% of the peak HR). The contribution of sympathetic and parasympathetic exercise tachycardia was determined in terms of differences in the time constant effects on the HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
14

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 34 publications
(51 reference statements)
2
15
0
14
Order By: Relevance
“…O 2 for the young group only, as well as an increase in power peak for both groups. This increase in aerobic capacity has been documented in other studies (10,15,16,21,22) for both anaerobic threshold and peak V . O 2 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…O 2 for the young group only, as well as an increase in power peak for both groups. This increase in aerobic capacity has been documented in other studies (10,15,16,21,22) for both anaerobic threshold and peak V . O 2 .…”
Section: Discussionsupporting
confidence: 83%
“…Concerning V . O 2 at the anaerobic threshold, the literature has also shown a decline of this parameter with advancing age (13) and there are studies indicating the occurrence of significant changes in aerobic capacity and autonomic changes in HR after aerobic training in middle-aged subjects (15,16).…”
Section: Introductionmentioning
confidence: 97%
“…It corresponds to a point above a determined power value when the production of lactic acid is greater than the capacity of its utilization by body tissues (1,14). AT shows a good correlation with V .…”
mentioning
confidence: 98%
“…In a study on post-menopausal women using DDET, Ribeiro et al (19) observed a loss of HR stability and a decrease in HR variability due to the prevalence of sympathetic activity on the sinus node. The inter-group differences in AT level are due to aging that markedly influences the cardiovascular system, promoting structural and functional changes (14). Takahashi et al (20), studying cardiac patients without the use of betablockers during physical exercise and with a discontinuous protocol, verified that by the adjustment of the semiparametric mathematical model to the HR data, the AT was identified at the power of 37.5 W and at HR of 100 bpm.…”
mentioning
confidence: 98%
See 1 more Smart Citation